О комплексной проблеме моментов на радиальных лучах - Загороднюк, С.М. (Журнал математической физики, анализа, геометрии, 2005)
The complex moment problem in the case when the support of the measure lies on the algebraic curves PN = {z є C : z^N-ž^N = 0}, N = 1, 2, 3,..., is studied. For N = 2, 3 the necessary and sufficient conditions of solvability are obtained and all solutions of the problem are described. It is shown how this problem for arbitrary N is connected with the Hamburger moment problem with parameters.